Antioxidant and cytoprotection effects of Solanum tuberosum (potato) on gastric mucosa in experimental animals - Sandoval-Vegas, Miguel (2010)
Background: There are therapeutic alternatives in Peru with empirical native products such as potato juice. Objectives: To assess the antioxidant capacity and the gastric mucosa cytoprotection effect by Solanum tuberosum juice. Design: Experimental. Institution: Research Center of Biochemistry and Nutrition, Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Biological materials: Solanum tuberosum, tomasa variety, and male albino rats. Methods: Oral solid fractions of supernatant and sediment from Solanum tuberosum juice were administered to fasting rats and an hour later, alcohol was given for gastric injury; gastric tissue was obtained by laparotomy. Oxidative stress was measured in the gastric mucosa by lipoperoxidation, formation of mucus by alcian blue, and the extent of protection by measuring lacerated areas in scanned image. Main outcome measures: Antioxidant capacity and gastric mucosa cytoprotection. Results: The 5 mL/kg supernatant produced greater oxidative stress protection; the 5 mL/kg pellet dose showed increased production of mucus, without exceeding controls. The 20 mL/kg precipitate produced greater cytoprotection, 73,8%. Conclusion: Supernatant fraction of Solanum tuberosum juice has antioxidant effect and the fraction of the sediment increased cytoprotective activity on gastric mucosa.